Caregiver-Child Co-Rumination and Treatment Outcomes in a Randomized Clinical Trial of Rumination-Focused Cognitive-Behavioral Therapy - A. Kaufman Erin; Xu Yizhe; Farstead Brian; Westlund Schreiner Mindy; Prunuske Jin; Bakian Amanda; L. Bessette Katie; A. Langenecker Scott; R. Watkins Edward (Journal of Depression And Therapy, 2025)
A number of developmental factors increase risk for adolescent rumination. This particular kind of repetitive negative thinking pattern often begins in the context of familial stressors and parental modeling. Though rumination can be effectively targeted with rumination-focused cognitive behavioral therapy (RF-CBT), it is unknown whether caregiver-child co-rumination (1) affects caregiver views of their child’s psychopathology, (2) or interferes with youth rumination- focused treatment. The present study uses data from a randomized clinical trial of RF-CBT to examine whether caregiver-child co-rumination, or caregivers’ own rumination patterns, are associated with bias in parental perception of their adolescent’s depression symptoms. We also examine if co-rumination scores at baseline moderate rumination scores for youth at treatment termination, and whether treatment effects dampen or decay more significantly post-treatment among youth with higher caregiver-child co-rumination. Youth (N = 76) were randomized to either 10-14 sessions of RF-CBT (n = 38) or treatment as usual (TAU; n = 38) and completed interviews and surveys at pre-treatment baseline, post-treatment, and 3-, 6-, 9-, and 12-month follow up. Results indicate that neither caregiver rumination nor co-rumination scores bias caregivers’ views of their child’s depression symptoms. In terms of reduction in child’s rumination scores, estimated treatment effects were larger for patients with higher baseline co- rumination scores, and there was no statistically significant difference in treatment effect decay over time in high versus low co-rumination groups. Results indicate co-rumination overall does not dampen the effect of RF-CBT, and those experiencing the highest levels of co-rumination may benefit most from treatment.
Keywords: rumination